Metis History and Experience and Residential Schools in Canada - Judy D. Daniels; Larry N. Chartrand; Tricia E. Logan (Aboriginal Healing Foundation, 2006)
A report foregrounding the experiences of Metis children in residential schools, and the issues they have faced and continue to face as a result.